Macroeconomic Stability in Bangladesh: Unraveling the Nexus between Exchange Rate, Inflation, and Export Dynamics through Nonlinear Modeling - Shahriar, A. H. M.; Biswas, Al Amin; Rumaly, Nishat; Rayhan, Md. Johir; Alam, Mohammad Jahangir; Golder, Uttam (International Journal of Economics and Financial Issues, 2024)
This study explores the effects of exchange rate and inflation on the export of goods and services in Bangladesh. Applying Nonlinear Autoregressive Distributed Lag (NARDL) model and using data from 1987 to 2021, in the case of a negative shock, this study finds a significant negative long-run association of exchange rate and inflation with export. Besides, in the case of positive shock, we see a meaningful positive relationship between inflation and exports. Following the findings, this study suggests exchange rate and inflation to ensure stability in Bangladesh’s economy through the issuance of new policies considering the reduction of inflationary pressures, formulation of contractionary monetary policy, recapping exchange-traded funds, and modification of exchange rate determination.